Environmental Learning Dalam Implementasi P5 Di Sekolah Dasar - Muslihah, Sri; Nurudin, Fajar; Rewinta, Rewinta; Aji, Setyo Bayu; Indayana, Sheiyla Anggraeni; Basuki, Sigit Rahmat; Sulistianingsih, Sulistianingsih; Nur, Tsalis Mukhammad; Nurfaidah, Vivi; Khoiriyyah, Wandan Hafidah; Hidayah, Ratna (Universitas Muhammadiyah Magelang, 2025)
The Kurikulum Merdeka emphasizes character education through the Pancasila Student Profile Strengthening Project (P5) to integrate Pancasila values into learning. This article aims to analyze the application of environmental learning in the P5 Program at SD Negeri Karangtanjung. The study employed a qualitative descriptive method through observation, interviews, and documentation. Results indicated that P5 activities such as chili planting, recycling materials, and ecoprinting support contextual learning, enhance critical thinking skills, and instill sustainability values in students. It is concluded that the P5 Program based on environmental learning effectively strengthens students' character and Pancasila profiles by engaging them in activities relevant to their surroundings.